Large-area, high-quality monolayer graphene from polystyrene at atmospheric pressure. (17th March 2017) - Xu, Junqi; Fu, Can; Sun, Haibin; Meng, Lanxiang; Xia, Yanjie; Zhang, Chongwu; Yi, Xiaolei; Yang, Wenchao; Guo, Pengfei; Wang, Chunlei; Liu, Jiangfeng
Abstract: Graphene films have been attracting great interest owing to their unique physical properties. In this paper, we develop an efficient method to prepare large-area monolayer graphene (97.5% coverage) by atmospheric pressure chemical vapor deposition on Cu foils using polystyrene in a short time (3 min). Raman spectroscopy, transmission electron microscopy and scanning electron microscopy are employed to confirm the thickness and uniformity of the graphene films. Graphene films on glass substrates show high optical transmittance and electrical conductivity. Magnetic transport studies demonstrate that the as-grown monolayer graphene exhibits a high carrier mobility of 3395 cm 2 V −1 s −1 at 25 K. On the basis of the analysis, it is concluded that our method is a simple, safe and versatile approach for the synthesis of monolayer graphene.